2007
DOI: 10.1021/jp071069x
|View full text |Cite
|
Sign up to set email alerts
|

Two-Photon Transitions in Quadrupolar and Branched Chromophores:  Experiment and Theory

Abstract: A combined experimental and theoretical study is conducted on a series of model compounds in order to assess the combined role of branching and charge symmetry on absorption, photoluminescence, and twophoton absorption (TPA) properties. The main issue of this study is to examine how branching of quadrupolar chomophores can lead to different consequences as compared to branching of dipolar chromophores. Hence, three structurally related π-conjugated quadrupolar chromophores symmetrically substituted with donor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
163
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(184 citation statements)
references
References 110 publications
(262 reference statements)
15
163
0
5
Order By: Relevance
“…25−27 In that case, significant cooperative enhancement of the twophoton cross-section of triple-branched structures could not be observed, in comparison with their counterpart linear moiety. 9,19,20,25 However, considering the short spatial distance between the branches and the identical transition moment of these moieties, it is still not likely that the branches are fully independent of each other. Energy transfer and interactions among the branches in the excited state should still exist within these compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25−27 In that case, significant cooperative enhancement of the twophoton cross-section of triple-branched structures could not be observed, in comparison with their counterpart linear moiety. 9,19,20,25 However, considering the short spatial distance between the branches and the identical transition moment of these moieties, it is still not likely that the branches are fully independent of each other. Energy transfer and interactions among the branches in the excited state should still exist within these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Both symmetry-breaking phenomena in excited state (caused by vibrational relaxation and solvation) and disorder-induced symmetry lowering (caused by ground state solute−solvent interaction) have been reported to contribute to the excitation localization. [25][26][27][42][43][44]64,65 In order to track down the excited state energy redistribution and the interbranch interaction of the multibranched molecules, it is instructive to determine the direction of molecular transition dipole moment and polarization of the spectrum.…”
mentioning
confidence: 99%
“…[33,36,57] In turn, exploitation of intermolecular interactions through branching strategies and the supramolecular approaches offers even more possibilities to tune or enhance TPA properties. This has already been demonstrated for branched chromophores built from the gathering of either dipolar [108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123] or quadrupolar [97,102,[124][125][126] sub-chromophores via common conjugated core moieties and multichromophore structures in which subchromophores interact only via electrostatic interactions. [127] Alternative routes such as those based on porphyrins, [128][129][130][131][132][133][134][135][136] oligomers and polymers [103,[137][138][139] have been explored as well.…”
Section: Introductionmentioning
confidence: 99%
“…The branched fluorescent probe (OM77) used in this study is shown in figure 1, designed for optimal near infra-red twophoton absorption and single photon fluorescence yield 9 . It has a substantial two-photon cross-section and a fast ground state vibrational relaxation time 10 which makes it an ideal candidate for single molecule STED 8 .…”
Section: Identification and Characterisation Of Chromophores For Singmentioning
confidence: 99%
“…Furthermore, OM77 is an efficient two-photon absorbing system in the visible where we have recently identified the onset of a giant two-photon resonance (ca. 12000GM at 570nm) 9 and the probability of DUMP excited fluorescence from ground state molecules needs to be minimized. To limit these effects, the DUMP pulses were temporally stretched using a grating pair to greater than 20 picoseconds.…”
Section: Experimental Apparatus Used For Bulk Sted Measurementsmentioning
confidence: 99%